Induction of Micronuclei in Germinating Onion Seed Root Tip Cells Irradiated with High Energy Heavy Ions - Takatsuji, Toshihiro; Takayanagi, Hiroki; Morishita, Kana; Nojima, Kumie; Furusawa, Yoshiya; Nakazawa, Yuka; Matsuse, Michiko; Akamatsu, Sakura; Hirano, Natsuko; Hirashima, Natsuko; Hotokezaka, Saori; Ijichi, Toyomi; et al. (Journal of radiation research, 2010)
Effects of high LET charged particles on a perfect in-vivo system are an essential theme for the study of the biological effects of radiation. Germinating onion seeds are independent complete organisms and the radiation induced micronuclei in the root chip cells can be examined quantitatively and theoretically. We irradiated with three types of high energy accelerated heavy ions germinating onion seeds using a synchrotron and observed micronuclei in the root tip cells. Micronuclei induction showed characteristic dose responses of an upward convex bell shape and a steep rise near zero doses for all types of the ions. The bell curve dose responses, however, could be explained by a simple mathematical model. A parameter in the model which indicates micronuclei induction frequency and another parameter which indicates induction frequency of lethal damages (or damages delaying cell divisions) per heavy ion track were both proportional to square of the LET. Because we suspected by-stander effect concerning the dose responses rising steeply near zero doses and tapering off for higher doses, we tested acute irradiation to remove time of information transmittance between cells using a single spill (about 0.3 s) of the synchrotron beam. No difference was detected between normal multiple spill irradiations and single spill.